GSK-3β regulates tumor growth and angiogenesis in human glioma cells - Zhao, Peng (Oncotarget, 2015)
BACKGROUND: Glioma accounts for the majority of primary malignant brain tumors in adults. METHODS: Glioma specimens and normal brain tissues were analyzed for the expression levels of GSK-3β and p-GSK-3β (Ser9) by tissue microarray analysis (TMA) and Western blotting. Glioma cells over-expressing GSK-3β were used to analyze biological functions both in vitro and in vivo. RESULTS: The levels of p-GSK-3β (Ser9), but not total GSK-3β, are significantly up-regulated in glioma tissues compared to normal tissues, and are significantly correlated with the glioma grades. Ectopic expression of GSK-3β decreased the phosphorylation levels of mTOR and p70S6K1; and inhibited β-catenin, HIF-1α and VEGF expression. Forced expression of GSK-3β in glioma cells significantly inhibited both tumor growth and angiogenesis in vivo. CONCLUSIONS: These results reveal that GSK-3β regulates mTOR/p70S6K1 signaling pathway and inhibits glioma progression in vivo; its inactivation via p-GSK-3β (Ser9) is associated with glioma development, which is new mechanism that may be helpful in developing GSK-3β-based treatment of glioma in the future.